The Role of AI, IoT, and E-Marketing in Enhancing the Sustainability and Competitiveness of MSMES - Sedana Putra, Komang Widhya; Laksmi, Kadek Wulandari; Ariwangsa, IGN Oka (Journal The Winners, 2024)
The research examined how the integration of Artificial Intelligence (AI), the Internet of Things (IoT), and e-marketing can enhance the sustainability and competitiveness of Micro, Small, and Medium Enterprises (MSMEs). It addresses the gap in existing literature regarding the synergistic effects of these technologies in overcoming resource constraints often faced by MSMEs during digital transformation. While previous research has focused on the individual benefits of AI or IoT, limited attention has been given to their combined impact on e-marketing and its influence on MSME sustainability. The research applied a quantitative approach to survey 200 MSMEs in Denpasar City through a Likert-scale questionnaire and analyzed with PLS-SEM version 4.0. The findings reveal that AI improves access to e-marketing channels and operational efficiency, while IoT enhances data analytics and automates business processes. Their integrated adoption significantly boosts digital marketing performance, positively affecting MSME sustainability. The challenges identified include the high costs and expertise required for effective implementation. Nonetheless, with appropriate investment and technical support, AI, IoT, and e-marketing synergy can make MSMEs more sustainable. From a managerial perspective, the long-term integration of these technologies into business strategies is critical for sustaining growth in the digital era.